PENGEMBANGAN APLIKASI ANDROID PADA SISTEM PENDETEKSI DINI KEBAKARAN LAHAN - Nada Araminta; Agus Wagyana (Universitas Tarumanagara, 2021)
Land fires are a tragedy that is difficult to control if the fire is large and can result in considerable losses. To be able to reduce the impact of losses due to land fires, an early warning is needed, therefore an application system is made that can detect land fires based on fire, smoke and temperature parameters. The methods used in the process of making this application are application system planning, application feature planning, layout design and java programming for each feature using Android Studio, configuration and programming on firebase, and finally the application can be released. This application uses firebase as a database platform that will store sensor data, user data, and cloud functions. The way this application works is that the application will display data on land conditions in real time, and when there is a change in status, the firebase will execute a command to provide a fire status warning via push notification in the form of a